An Unprecedented Efficiency with Approaching 21% Enabled by Additive-Assisted Layer-by-Layer Processing in Organic Solar Cells - Xu, Shuai; Zhang, Youdi; Sun, Yanna; Cheng, Pei; Yao, Zhaoyang; Li, Ning; Ye, Long; Zuo, Lijian; Gao, Ke (Nano-Micro Letters, 2024)
Recently published in Joule, Feng Liu and colleagues from Shanghai Jiaotong University reported a record-breaking 20.8% power conversion efficiency in organic solar cells (OSCs) with an interpenetrating fibril network active layer morphology, featuring a bulk p-i-n structure and proper vertical segregation achieved through additive-assisted layer-by-layer deposition. This optimized hierarchical gradient fibrillar morphology and optical management synergistically facilitates exciton diffusion, reduces recombination losses, and enhances light capture capability. This approach not only offers a solution to achieving high-efficiency devices but also demonstrates the potential for commercial applications of OSCs. Highlights: 1 Additive-assisted layer-by-layer (LBL) deposition enables organic solar cells to achieve an unprecedented power conversion efficiency of 20.8%, the highest efficiency to date. 2 The gradient fibrillar morphology enabled by additive-assisted LBL processing promotes the formation of bulk p-i-n structure, improving exciton and carrier diffusion, and reducing recombination losses. 3 The wrinkle pattern morphology achieved by additive-assisted LBL processing is constructed to enhance the light capture capability.